RECONCILING THE GENERAL AND THE UNIQUE AREA STUDIES, CASE STUDIES, AND HISTORY VERSUS THEORETICAL SOCIAL SCIENCE - F. Eidlin (Сравнительная политика, 2015)
The article examines the problem of relations between the General and the Unique in the social and political sciences. The author highlights the different views on this perspective: some scientists explain specifi c cases by bringing them under general theories and laws while others researchers emphasize that each case, each phenomenon is unique and shouldn’t be generalization. The author theorizes that there is a methodological bridge between the generalizing spirit of social science and uniqueness of events and cases.